Pleuropulmonary lesions, ergotamines and asbestos exposure - Hillerdal, Gunnar; Rask-Andersen, Anna (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'This study investigated the possibility of pleuropulmonary lesions, which can occur as rare but serious side effects of different ergot drugs, occurring more commonly in persons earlier exposed to asbestos. ' ' METHODS ': 'All reports of pleuropulmonary side effects of the ergot drugs used in Sweden in the Swedish side effect registry from 1985 to 2003 were studied. In addition, the literature was reviewed. ' ' RESULTS ': 'In the registry, 47 men and 3 women were found. Of the men, 24 were exposed to asbestos, and 2 denied such exposure; 2 of the 3 women were exposed. In the literature, 111 patients were found—32 had confirmed exposure and 15 denied it. For most of the patients, it was not possible to determine exposure. ' ' CONCLUSIONS ': 'Enough evidence exists to postulate that earlier asbestos exposure in combination with the intake of ergot drugs can cause pleuropulmonary lesions.
Keywords: asbestos exposure; bromocriptine; ergotamine; literature review; methysergide; pleural effusion; pleuropulmonary lesion; registry study; systemic reaction